Estrategias urbanas aplicadas al aprovechamiento efectivo de las áreas de cesión en el municipio de Palmira. - Lozano Gómez, Karen Tatiana (Universidad Antonio Nariño, 2021)
During the growth and development of Colombian cities, the interest and need to generate mandatory assignments has increased, which should be pillars of public space within cities that promote culture, sports and the economy and socialization.